2016
DOI: 10.3390/lubricants4020022
|View full text |Cite
|
Sign up to set email alerts
|

Towards Phosphorus Free Ionic Liquid Anti-Wear Lubricant Additives

Abstract: Abstract:The development of improved anti-wear additives would enable the use of lower viscosity oils that would lead to improved efficiency. Ionic liquids have the potential to be this type of new anti-wear additive. However, currently the best performing ionic liquids that are miscible in non-polar base oils, the phosphonium phosphates, contain phosphorus on both the cation and anion. Manufacturers are seeking to reduce the presence of phosphorus in oils. Here, as a first step towards phosphorus-free anti-we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Although several ILs have shown good performance as neat lubricants, the choice of ILs as lubricant additives is relatively restricted owing to their limited solubility in lubricating oils. Researchers reporting lubrication enhancement through ILs admixed with oils, ,, have highlighted the importance of developing oil-soluble ILs. ILs having quaternary structures with long hydrocarbon chains on both cations and anions have shown good miscibility with nonpolar hydrocarbon oils .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several ILs have shown good performance as neat lubricants, the choice of ILs as lubricant additives is relatively restricted owing to their limited solubility in lubricating oils. Researchers reporting lubrication enhancement through ILs admixed with oils, ,, have highlighted the importance of developing oil-soluble ILs. ILs having quaternary structures with long hydrocarbon chains on both cations and anions have shown good miscibility with nonpolar hydrocarbon oils .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, at high temperatures and pressures, halogenated ILs have been demonstrated to readily undergo hydrolysis with ambient water, resulting in the formation of toxic and corrosive halides, , which can shorten the lifetime of machine components and contribute to enhanced wear or system failure. In the past decade, these concerns have driven the development of nonhalogenated ILs for tribological purposes. , ,, ILs with phosphate and phosphinate anions have emerged as the popular candidates, largely because of the presence of tribo-active phosphorus and their good miscibility with oils. ,,, ,,, , Phosphinate-based ILs have been reported to reduce friction on both the nano- and macroscale, in atomic force microscopy (AFM) and pin-on-disk experiments, respectively, when used in very low concentrations in oil. ,, Meanwhile, ILs with phosphate anions have shown improved friction and wear when used as additives in various oils. ,,,,, More recently, orthoborates have attracted attention as a new class of anions for lubrication applications and have been demonstrated to exhibit excellent friction reduction and wear protection, both as neat lubricants and as additives in oils. , When dispersed in other (more polar) solvents, they have also exhibited high surface activity, providing highly lubricious interfacial structures. …”
Section: Introductionmentioning
confidence: 99%
“…Compared to commercial lubricating oils of similar viscosities, this IL shows significantly improved friction coefficient and thermal stability. Studies from our group and others have shown that [P6, 6,6,14] + cation based ILs are potential additives for hydrocarbon base oils for a variety of surfaces [19][20][21][22][23][24][25][26][27]. As little as 2 mol% IL dissolved in a base oil lubricates as effectively as the pure IL, and low concentration IL-oil mixtures are much more effective lubricants than the pure base oil [20][21][22], or oils with traditional additives [22,28].…”
Section: Introductionmentioning
confidence: 99%
“…Room-temperature Ionic Liquids (ILs) are salt structures consisting of large cation and anion moieties, which are characterized by melting temperatures below 100 °C. In tribological applications, the ILs have demonstrated superior performance as lubricants under both mixed and boundary conditions [1][2][3][4][5][6][7][8][9]. Under severe environments, in space and at high temperatures IL-base lubricants are especially propitious due to their exceptional tribochemical thermal and stability, both oxidative and nonoxidative [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%